Apparent digestibility coefficients for amino acids of feed ingredients in tambaqui (Colossoma macropomum) diets - Torres do Nascimento, Thiago Matias [UNESP]; Buzollo, Hellen [UNESP]; Goncalves de Sandre, Lidiane Cristina [UNESP]; Neira, Ligia Maria [UNESP]; Abimorad, Eduardo Gianini; Carneiro, Dalton Jose [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2020)
This study evaluated the apparent digestibility coefficients (ADC) of essential (EAA) and non-essential (NEAA) amino acids of 13 ingredients for tambaqui (Colossoma macropomum) diets. Proteic and energetic ingredients were analyzed separately. The trial with energetic and proteic ingredients were arranged in a randomized block design, with four replicates: energetic ingredients (corn, wheat bran, broken rice, and sorghum) with four treatments, whereas proteic ingredients (corn gluten meal, soybean meal, poultry byproduct meal, salmon meal, fish meal [tilapia processing residue], wheat gluten meal, feather meal, cottonseed meal, and alcohol yeast [spray dried]) with nine treatments. Each block was considered as one round of fecal collection. A total of 420 tambaqui juveniles (mean initial weight: 70 +/- 8.58 g) were used. Among energetic ingredients, corn (94.6%) and wheat bran (91.9%) had the highest ADCEAA, followed by broken rice (75.7%), and sorghum (72.8%). On average, ADCEAA and ADCNEAA values of proteic ingredients were 79.5-98.5%, except for alcohol yeast (ADCEAA: 68.4 and ADCNEAA: 76.7%). Tryptophan was the first limiting amino acid in most ingredients tested and had the lowest chemical scores (0.06-0.51), except for wheat bran, corn gluten meal, and soybean meal, in which lysine was the first limiting amino acid. Soybean meal had the highest digestible essential amino acid index (EAAI: 1.02) and the most balanced amino acid profile, whereas wheat gluten meal had the lowest EAAI (0.48). Overall, tambaqui was very efficient to digest proteic and energetic ingredients.
Keywords: amino acids; chemical score; digestibility; feed ingredients; fish; nutrition